PEMBERDAYAAN MASYARAKAT KELURAHAN PELAMBUAN MELALUI PROGRAM PENDIDIKAN NONFORMAL DAN LIFESKILLS MENJAHIT BAGI PESERTA DIDIK PAKET C DI PKBM WARRAHMAH - Ahmad Baihaqi (Al-Manba, 2025)
Non-formal education programs serve as a strategic effort to improve the quality of human resources, particularly for communities with limited access to formal education. This article discusses the empowerment of the Pelambuan Subdistrict community through a life skills-based sewing program provided to Package C students at PKBM Warrahmah. The program aims to equip participants with practical skills that can directly enhance their economic independence. The method employed is a participatory approach, involving hands-on sewing training from basic techniques to the production of simple, marketable items. The results show significant improvement in participants' sewing abilities, self-confidence, and motivation to pursue entrepreneurship. This program demonstrates that non-formal, skills-based education can be an effective solution for community empowerment and reducing unemployment, especially in densely populated urban areas.